2013
DOI: 10.1038/ismej.2013.177
|View full text |Cite
|
Sign up to set email alerts
|

Distinct responses of soil microbial communities to elevated CO2 and O3 in a soybean agro-ecosystem

Abstract: The concentrations of atmospheric carbon dioxide (CO 2 ) and tropospheric ozone (O 3 ) have been rising due to human activities. However, little is known about how such increases influence soil microbial communities. We hypothesized that elevated CO 2 (eCO 2 ) and elevated O 3 (eO 3 ) would significantly affect the functional composition, structure and metabolic potential of soil microbial communities, and that various functional groups would respond to such atmospheric changes differentially. To test these hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
59
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 81 publications
9
59
3
Order By: Relevance
“…A previous study in an agro-ecosystem also demonstrated the positive correlation between crop yield and the abundance of genes involved in C degradation (He et al, 2014), supporting the close relationship between microbial C utilization potential and the returned plant resources. With regard to the specific C components, increased aboveground plant biomass tended to stimulate the genes responsible for recalcitrant C degradation, as illustrated by stepwise regression, whereas the genes/enzymes involved in labile C degradation showed no response to plant biomass and selected soil variables (Table 4).…”
Section: Discussionmentioning
confidence: 90%
“…A previous study in an agro-ecosystem also demonstrated the positive correlation between crop yield and the abundance of genes involved in C degradation (He et al, 2014), supporting the close relationship between microbial C utilization potential and the returned plant resources. With regard to the specific C components, increased aboveground plant biomass tended to stimulate the genes responsible for recalcitrant C degradation, as illustrated by stepwise regression, whereas the genes/enzymes involved in labile C degradation showed no response to plant biomass and selected soil variables (Table 4).…”
Section: Discussionmentioning
confidence: 90%
“…The results showed that the overall functional composition and structure of the soil microbial community shifted under eO 3 . Key functional genes involved in C fixation, nitrogen fixation, denitrification and N mineralization were suppressed under eO 3 , and those involved in C degradation and CH 4 generation remained unchanged under eO 3 (He et al, 2013). These variable responses of the microbial community to eO 3 may be attributed to numerous factors, including different species, different levels of O 3 exposure and different sampling procedures at different growth stages.…”
Section: Shannon-weinner Diversity Richnessmentioning
confidence: 97%
“…In that study, genetic profiling based on single-strand conformation polymorphisms (SSCP) revealed that the different SSCP profiles generated from the bacterial community of the rhizospheres from O 3 -stressed and control plants were very similar and were not distinguished by statistical methods, which indicated that elevated levels of O 3 did not select for a different bacterial community composition. He et al (2013) also analyzed 96 soil samples from a soybean free-air CO 2 enrichment (SoyFACE) experimental site using a comprehensive functional gene microarray (GeoChip 3.0, MWG Biotech Inc., High Point, North Carolina, USA). The results showed that the overall functional composition and structure of the soil microbial community shifted under eO 3 .…”
Section: Shannon-weinner Diversity Richnessmentioning
confidence: 99%
“…1000 μmol l −1 by the end of this century (IPCC 2013). An elevated CO 2 concentration has significant influence on plant growth and development, soil carbon (C) and nitrogen (N) dynamics as well as agricultural ecosystem function (He et al 2014;Aljazairi et al 2015). It is well known that C and N fixation, decomposition, metabolism, and dynamics in the ecosystem are mediated by soil microbes (Treseder et al 2003;He et al 2014).…”
Section: Introductionmentioning
confidence: 99%